2017
DOI: 10.1016/j.joto.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation outcomes in children with common cavity deformity; a retrospective study

Abstract: ObjectiveA common cavity deformity (CCD) is a deformed inner ear in which the cochlea and vestibule are confluent forming a common rudimentary cystic cavity that results in profound hearing loss. There are few studies paying attention to common cavity. Our group is engrossed in observing the improvement of auditory and verbal abilities in children who have received cochlear implantation (CI), and comparing these targets between children with common cavity and normal inner ear structure.Material and methodsA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…Our study also identified a poor prognosis, especially in language performance. Nevertheless, there are obvious advantages of cochlear implantation that justify the risks of the surgery [ 14 , 15 ]. Perilymph gushers have been commonly reported in previous studies; however, none of the enrolled patients in this study had severe gushers that required extensive sealing [ 9 , 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified a poor prognosis, especially in language performance. Nevertheless, there are obvious advantages of cochlear implantation that justify the risks of the surgery [ 14 , 15 ]. Perilymph gushers have been commonly reported in previous studies; however, none of the enrolled patients in this study had severe gushers that required extensive sealing [ 9 , 11 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies included a preoperative and postoperative CAP score. Zhang et al evaluated children with CC deformity against a control group matched in sex, age, and time of implantation (n = 6) [20]. Both the control and IEM groups showed improvement, though patients with CC deformity improved significantly less than those with normal inner ear anatomy.…”
Section: Cap Scorementioning
confidence: 99%
“…Both the control and IEM groups showed improvement, though patients with CC deformity improved significantly less than those with normal inner ear anatomy. The mean CAP improvement in patients with IEMs was 3.50 compared to 9.50 in the control group [20]. Melo et al assessed CAP-II scores in patients with and without IEMs that received CIs.…”
Section: Cap Scorementioning
confidence: 99%
“…-Dị dạng khoang chung là dị dạng tiền đình và ốc tai hợp lưu tạo thành một khoang chung, không có trụ ốc ở trung tâm, có dây TK ốc taitiền đình chung. Một số tác giả cho thấy cấy OTĐT với BN dị dạng khoang chung là giải pháp an toàn và hiệu quả, mặc dù phẫu thuật khó khăn [8]. Chúng tôi có 7 tai dị dạng khoang chung, các tai này đều có kích thước lớn có thể đặt được điện cực vào khoang chung vì vậy có thể cấy OTĐT trong những trường hợp này.…”
Section: Kết Quả Nghiên Cứuunclassified